Assessment of Senior Secondary Schools on the Status of Field Practical in Animal Agriculture in Osun State, Nigeria - Oyeleye, Olubisi O.; Balogun, O. T.; Makun, A. (Nigerian Journal of Animal Science, 2023)
he impact of inclusion of Animal husbandry (ANH) as an Applied science and a Vocational study in the Senior Secondary school curriculum was assessed. The assessment was carried out for four years (2014 to 2017) in the state of Osun, Nigeria. The following criteria were set as the standard of assessment: housing/facility availability, feeds and feeding regime, farm sanitation, health status, record keeping and responses of candidates to field practical questions in Animal agriculture. The study used survey methodology through structured scoring manuals and face to face interviews. Data collated were analysed using descriptive statistics and F-test to determine levels of significance among the means at P<0.05. The results showed that only 49 % of the schools had adequate farm houses, 12 % used self-formulated feeds only, over 90 % of the schools scored above 70 % in farm sanitation, 31.5 % kept appropriate records while the scores in the responses of candidates to field practical questions in all the criteria set showed that candidates demonstrated high aptitude to acquire and excel in practical vocational training as evident in their extremely good performance (>75 %). The study suggests urgency for investment in vocational and entrepreneurship subjects which reserve the capacity to make students self-reliant economically and also supply requisite skills for industries through today’s stereotypical educational system.